2005
DOI: 10.1121/1.1828499
|View full text |Cite
|
Sign up to set email alerts
|

Object-related brain potentials associated with the perceptual segregation of a dichotically embedded pitch

Abstract: The cortical mechanisms of perceptual segregation of concurrent sound sources were examined, based on binaural detection of interaural timing differences. Auditory event-related potentials were measured from 11 healthy subjects. Binaural stimuli were created by introducing a dichotic delay of 500-ms duration to a narrow frequency region within a broadband noise, and resulted in a perception of a centrally located noise and a right-lateralized pitch (dichotic pitch). In separate listening conditions, subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
57
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 24 publications
(16 reference statements)
12
57
1
1
Order By: Relevance
“…The negative difference was also evident in response to test pairs near depressed buildup echo threshold when listeners reported hearing compared to not hearing the lag sound. This ERP effect is similar in timing, distribution, and amplitude to that observed when participants report hearing two sound sources compared to one sound source for clicks near single-pair echo threshold in the precedence effect (Sanders et al, 2008), when a mistuned harmonic which is not sufficient to produce perception of two simultaneous pitches is presented from a distinct location (McDonald and Alain, 2005), and various acoustic manipulations that result in listeners hearing two simultaneous pitches compared to a single pitch (Alain et al, 2001;Alain et al, 2002;Alain and Izenbert, 2003;Dyson and Alain, 2004;Hautus and Johnson, 2005;Hiraumi et al, 2005;Chait et al, 2006). This difference in ERPs observed when listeners perceive two compared to one auditory event, regardless of the feature that separates the two events (location or pitch) and whether perception is driven by physical differences in the stimuli or not, has been termed the ORN.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The negative difference was also evident in response to test pairs near depressed buildup echo threshold when listeners reported hearing compared to not hearing the lag sound. This ERP effect is similar in timing, distribution, and amplitude to that observed when participants report hearing two sound sources compared to one sound source for clicks near single-pair echo threshold in the precedence effect (Sanders et al, 2008), when a mistuned harmonic which is not sufficient to produce perception of two simultaneous pitches is presented from a distinct location (McDonald and Alain, 2005), and various acoustic manipulations that result in listeners hearing two simultaneous pitches compared to a single pitch (Alain et al, 2001;Alain et al, 2002;Alain and Izenbert, 2003;Dyson and Alain, 2004;Hautus and Johnson, 2005;Hiraumi et al, 2005;Chait et al, 2006). This difference in ERPs observed when listeners perceive two compared to one auditory event, regardless of the feature that separates the two events (location or pitch) and whether perception is driven by physical differences in the stimuli or not, has been termed the ORN.…”
Section: Discussionmentioning
confidence: 70%
“…Specifically, mistuning a single frequency in a harmonic complex to the extent that listeners report hearing two simultaneously presented distinct pitches (one based on the fundamental frequency of the complex and one on the frequency of the mistuned harmonic), elicited a larger negativity 100-250 ms over anterior and medial regions (Alain et al, 2001;Dyson et al, 2005). The ORN has also been reported in studies that induced two-sound perception through the use of dichotic pitch stimuli (Johnson et al, 2003;Hautus and Johnson, 2005;Chait et al, 2006). Further, when the amount of harmonic mistuning was not enough to result in perception of two distinct pitches, presenting the mistuned harmonic from a different location elicited the ORN (McDonald and Alain, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Event-related brain potential (ERP) studies have revealed an attention-independent component that peaks at ϳ150 ms after sound onset, referred to as the object-related negativity (ORN) (Alain et al, 2001b(Alain et al, , 2002Alain and Izenberg, 2003;Dyson et al, 2005). The ORN overlaps in time with the N1 and P2 deflections elicited by sound onset and is best illustrated by the difference wave between ERPs elicited by complex sounds that are grouped into one auditory object and those elicited by complex sounds that are segregated into two distinct auditory objects based on frequency periodicity (Alain et al, 2001b(Alain et al, , 2002Alain and Izenberg, 2003), interaural time difference (Johnson et al, 2003;Hautus and Johnson, 2005;McDonald and Alain, 2005), or both (McDonald and Alain, 2005). Recently, Snyder and Alain (2005) found an age-related decline in concurrent vowel identification, which was paralleled by a decrease in neural activity associated with this task.…”
Section: Introductionmentioning
confidence: 99%
“…8). Previous studies have shown that, as with the ORN, the P400 component is tightly linked to concurrent sound segregation, but unlike the ORN is elicited only when listeners are required to actively attend and generate behavioural responses to sounds (Alain et al, 2002;Hautus & Johnson, 2005). As such, it seems clear that it indexes a controlled, rather than automatic, level of processing associated with the identification of concurrent sound sources and selection of a behavioural response (Alain et al, 2002).…”
Section: The P400 and Perceptual Contextmentioning
confidence: 99%
“…Using EEG and MEG to measure brain activity in human listeners, we have found that the hearing out of dichotic pitches elicits a sequence of auditory cortical responses over a time window of some 150-400 ms after the onset of a dichotically-embedded pitch. In a series of experiments (Johnson et al, 2003;Hautus & Johnson, 2005;Johnson et al, 2007;Johnson & Hautus, 2010) we have shown that these responses correspond to functionally distinct stages of auditory scene analysis. Our data provide new insights into the nature, sequencing and timing of those stages.…”
Section: Introductionmentioning
confidence: 99%